Sr–Nd isotope data of basement rocks from the northernmost argentine Precordillera and its implications for the early Paleozoic evolution of SW Gondwana margin - Martina, Federico (2014)
The Precordillera terrane (Cuyania) in western Argentina is commonly accepted as an exotic fragmentderived from Laurentia in the Early Paleozoic. Evidence supporting such an interpretation is manly basedon similarities in the sedimentary cover successions and their paleontological content. Little is knownabout the basement of the Precordillera terrane. Its isotopic characterization is essential to betterconstrain the present areal distribution of the terrane and it may provide more insight into the pre-rifting evolution of the Precordillera terrane along the Iapetan margin of Laurentia. We present newSr and Nd isotope data of pre-Late Ordovician meta-igneous rocks from the Río Bonete region in NWArgentina, interpreted as the northernmost extent of the Precordillera. The Nd systematics of the RíoBonete basement rocks including greenschists and metagabbros (εNd(470)¼þ2.14e 0.19;TDM¼0.99e1.2 Ga), a garnet-amphibolite (εNd(470)¼ 0.53;TDM¼1.32 Ga) and a quartz-phyllite (εNd(470)¼ 3.83;TDM¼1.55 Ga), are similar to other pre-Ordovician meta-igneous rocks from Sierra de Umango, Pie dePalo and the Ullum xenoliths, usually interpreted as the basement of the Precordillera terrane. Nd modelages around 1.2 Ga are also typical from the Mesoproterozoic Grenvillian basement of southern NorthAmerica, currently exposed in the Llano region. In addition, the greenschists and metagabbros show arobust correlation with the Late Neoproterozoic Catoctin volcanics in the central Appalachians. The Srisotope data (when not disturbed) also supports this novel interpretation and suggests the presence ofthe Blue Ridge rifting event in Precordillera. According to our interpretation, some lithotypes includedwithin the basement complex of the Río Bonete area belonged to the basement of the Precordilleraterrane supporting previous correlation between both regions.